Socio-natural Disasters and Poverty: An Analysis from Emergency Decrees Issued in Chile - Elia Sepúlveda; Roxana Contreras; Alejandra Mora Castillo (Social Work & Society, 2021)
The objective of this article is to determine the type and location of the main natural disasters occurred in Chile between 1990 and 2017. From the time of occurrence and their geographical distribution we analyse their link to regional poverty. A documentary research was done from the classification and analysis of the decrees of emergency issued in Chile during that period. This was done together with the statistical study of the variation of regional poverty, obtained from the Chilean National Socioeconomic Characterization Survey (CASEN). It was possible to conclude that the majority of the regions where a decree was issued, had a percentage of poverty above the national average.